On the limit theorems when the limit law is stable - Statulevičius, V. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. А. Статулявичюс. О предельных теоремах в случае устойчивого предельного закона V. Statulevičius. Ribinių teoremų stabilaus ribinio dėsnio atveju klausimu